Work-Related Injuries with Child Labor in Iran - Hosseinpour, Mehrdad; Mohammadzadeh, Mahdi; Atoofi, Maryam (European Journal of Pediatric Surgery, 2014)
Aim Accurate present-day child labor information is difficult to obtain. The aim of this study was to evaluate the characteristics of child labor patients according to worker status and identify the proportion of work-related injuries that could be prevented by protection devices.Patients and Methods This study was performed in one of the largest pediatric trauma center in the central part of Iran. In a prospective case series study, injured children with age less than 15 years who were consecutively admitted to the trauma center for management of their trauma were evaluated. In each patient data such as age, sex, worker status, anatomic site of injury, and costs were collected.Results In this study, a total of 127 children were evaluated. Most of the injuries (80.3%) occurred in urban areas. In most of the injured patients, the main reason of working was to help pay own family debts or supplement family income. Industrial workroom was the most common place for injury (58.2%). Falling from height or in horizontal surface was the most common mechanism of injury (44%). None of the patients had preventable device at the time of injury. Cuts (49.6%) were the most commonly reported injuries. The lengths of hospitalization were 1.23 + 0.88 days. There was no death reported in our cases. The mean of cost of hospitalization was US $29.9 ± 20.36.Conclusion Our study showed that child labor injury in the central part of Iran mainly occurred in nonagricultural sector due to falling. These injuries are nonfatal and might be prevented by protective equipment.
Keywords: child labor; hazardous work; work injury